Service Quality Improvement Strategy to Enhance Guest Satisfaction at Ayung Valley Restaurant, The Royal Pita Maha Hotel Ubud, Bali: Strategi Peningkatan Kualitas Pelayanan guna Meningkatkan Kepuasan Tamu di Restoran Ayung Valley pada Hotel the Royal Pita Maha Ubud, Bali - Pratama, I Putu Yudha; Sulastri, Ida Ayu Putu; Putra, I Nengah Sandi Artha (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
Restaurant service quality in a five-star hotel is a primary determinant of guest satisfaction and loyalty. This study aims to analyze the service quality improvement strategy at Ayung Valley Restaurant, The Royal Pita Maha Hotel Ubud, Bali; identify the challenges encountered; and describe the efforts undertaken to overcome them. A qualitative descriptive approach was employed, using direct observation based on SERVQUAL dimensions (tangibles, reliability, responsiveness, assurance, and empathy), in-depth interviews with the restaurant manager, supervisor, and service staff, and documentation during the research period. The results show that the restaurant has implemented several service quality improvement strategies including periodic staff training, SOP-based service procedures, evaluation of guest feedback, and effective communication between management and service staff. However, challenges were identified including insufficient variety of breakfast menu items, inadequate preparation resulting in delayed service during morning sessions, inconsistency between the Indian cuisine label and its actual taste, and noise from external music disturbing the dining atmosphere. Efforts to overcome these challenges include structured menu diversification programs, pre-opening briefings and preparation checks, involving specialized culinary expertise for cuisine authenticity, and operational renovation to reduce noise. This study concludes that a systematic, multi-dimensional service quality improvement strategy is essential for sustaining competitive advantage and guest satisfaction at luxury resort restaurants in Ubud, Bali.